Perceptions of Leadership Effectiveness among the African Diaspora in Canada and USA. Issue 1 (2nd January 2019) - Galperin, Bella L.; Michaud, James; Senaji, Thomas A.; Taleb, Ali
ABSTRACT: This paper investigates the applicability of leadership effectiveness factors developed in Africa to the African diaspora and compares/contrasts perceptions of effective leadership in Canada and the USA. Using quantitative data from the LEAD project, our findings suggest that the African diaspora fully relates to neither Western conceptualization nor African philosophies of leadership. The factors that achieved a good fit in both Canada and the US related to being a knowledgeable leader and effective communication skills. This paper contributes to managing a more diverse and inclusive workplace in the diaspora, and informing leadership theory and practice in Africa.